Learning by Doing, and Doing it Right – Building a Multi-Dimensional Social Determinants of Health Curriculum in a Rural Internal Medicine Residency - Sophia Zhang; Yibei Zhu; Lara Parrilla; Kaili Du (Journal of Medical Education and Curricular Development)
OBJECTIVES While there has been increasing awareness of the importance of social determinants of health (SDOH) learning for internal medicine residents and physicians, only a few residency programs have incorporated training into their curricula. For those who did, the curricula were often didactic and lacked action-driven components or community partnership. Therefore, we built an experiential SDOH curriculum with an action-driven element and emphasis on community partnerships in a newly established residency program in rural New York. METHODS Over 24 months, 22 internal medicine residents were engaged in SDOH lectures, workshops, and action-driven learning through implementing screening tools in residency clinics and working with community partners. After the curriculum, residents’ competency in addressing SDOH needs was assessed through Likert-scale questionnaires. Focused interviews were conducted among participating residents and faculty to obtain qualitative feedback on the curriculum. RESULTS Participating resident physicians demonstrated competency in recognizing and addressing SDOH needs after curriculum completion (mean competency score = 4.04). A significant increase in residents’ self-rated confidence in addressing SDOH was observed after training ( P  = .002). Residents reported enhanced relationships with patients, effective utilization of community resources, and readiness to apply SDOH knowledge and skills to their future practice. Residents and faculty also discussed the SDOH challenges unique to rural primary care through their experiences. CONCLUSION This curriculum provides insights into an educational framework that improves residents’ SDOH awareness, integrates SDOH into resident physicians’ daily practice, and facilitates community collaboration. While challenges unique to rural primary care exist, this curriculum demonstrated the feasibility of longitudinal, action-driven, and community-centered SDOH education in rural areas that may inform future programs’ curricular design.